Sea Level Rise in Indonesia and Legal Certainty of Sea Territory: Implications of the ICJ Advisory Opinion of 23 July 2025 Under UNCLOS 1982 on Baselines and Delimitation - Ria Tri Vinata (Journal of Maritime Policy Science, 2026)
Sea level rise due to climate change challenges the legal certainty of Indonesia's maritime space as changes to the coastline have the potential to affect delimitation. This article aims to analyse the implications of the International Court of Justice (ICJ) Advisory Opinion 23 July 2025 on the legal certainty of the base line, outer limits of the maritime zone, and delimitation, by placing Indonesia as an archipelagic country vulnerable to abrasion, tidal dynamics, and the risk of jurisdictional disputes. The research method used is juridical-normative through document study and textual and systematic interpretation of UNCLOS provisions on the base line, publicity and deposit of maps/list of geographical coordinates, and delimitation provisions along with legal principles of maritime boundary agreements. The analysis shows that physical coastal changes do not necessarily give rise to an obligation to update maps or coordinate lists automatically and recurrently once a maritime zone is duly established. This finding confirms that the published and deposited coordinate list serves as a verifiable jurisdictional instrument, subject to compliance with UNCLOS and the principle of lawful maintenance. In the realm of delimitation, the stability of treaty-based boundaries is maintained in principle, while the greatest vulnerability lies in segments that are not yet finalised or effective. This article recommends a two-track strategy for Indonesia: maintaining legal boundary certainty through strengthening coordinate and deposit governance, while updating hydrographic information for navigation safety without changing the legal position of boundaries, and prioritising the completion and effectiveness of boundary agreements in potentially overlapping areas.